Nebulette mutations are associated with dilated cardiomyopathy and endocardial fibroelastosis - Purevjav, Enkhsaikhan; Varela, Jaquelin; Morgado, Micaela; Kearney, Debra L.; Li, Hua; Taylor, Michael D.; Arimura, Takuro; Moncman, Carole L.; McKenna, William; Murphy, Ross T.; Labeit, Siegfried; Vatta, Matteo; et al. (Journal of the American College of Cardiology, 2010)
Objectives - Four variants (K60N, Q128R, G202R, and A592E) in the nebulette gene were identified in patients with dilated cardiomyopathy (DCM) and endocardial fibroelastosis. We sought to determine if these mutations are cardiomyopathy causing. - Background - Nebulette aligns thin filaments and connects them with the myocardial Z-disk, playing a role in mechanosensation. - Methods - We generated transgenic mice with cardiac-restricted overexpression of human wild-type or mutant nebulette. Chimera and transgenic mice were examined at 4, 6, and 12 months of age by echocardiography and cardiac magnetic resonance imaging. The hearts from embryos and adult mice were assessed by histopathologic, immunohistochemical, ultrastructural, and protein analyses. Rat H9C2 cardiomyoblasts with transient expression of nebulette underwent cyclic mechanical strain. - Results - We identified lethal cardiac structural abnormalities in mutant embryonic hearts (K60N and Q128R). Founders of the mutant mouse lines developed DCM with severe heart failure. An irregular localization pattern for nebulette and impaired desmin expression were noted in the proband and chimeric Q128R mice. Mutant G202R and A592E mice exhibited left ventricular dilation and impaired function with specific changes in I-band and Z-disk proteins by 6 months of age. The mutations modulated distribution of nebulette in the sarcomere and Z-disk during stretch of H9C2 cells. - Conclusions - Nebulette is a new susceptibility gene for endocardial fibroelastosis and DCM. Different mutations in nebulette trigger specific mechanisms, converging to a common pathological cascade leading to endocardial fibroelastosis and DCM.
Gesehen am 08.05.2023